(untitled) (SCIENCE TIME JOURNAL, 2026)
This article examines contemporary approaches to emoji semantics in digital communication. The study focuses on three major theoretical frameworks: cognitive, pragmatic, and semiotic approaches. Through a qualitative comparative analysis of recent linguistic research, the paper identifies the key principles, strengths, and limitations of each approach. The findings demonstrate that emoji function as multimodal meaning-making units that extend beyond traditional linguistic boundaries. It is argued that emoji semantics is inherently dynamic, context-dependent, and shaped by the interaction of visual and verbal elements. The study contributes to the development of modern linguistic theory by proposing an integrated perspective on emoji interpretation.